2003
DOI: 10.1007/s00432-003-0490-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor-targeted therapy potentiates lovastatin-induced apoptosis in head and neck squamous cell carcinoma cells

Abstract: These results demonstrated the ability of EGFR pathway inhibitors to potentiate lovastatin-induced apoptosis and suggested that lovastatin may target the EGFR pathway in HNSCC cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 43 publications
1
44
0
Order By: Relevance
“…Lovastatin potentiated the antitumor effects of cisplatin in cellular and murine models of melanoma (Feleszko et al, 1998), increasing, at least partially, the apoptotic effect of oxaliplatin in human head and neck squamous cell carcinoma (SCC) (Mantha et al, 2003). In human colon cancer cell lines, the pretreatment with lovastatin increased the apoptotic death induced by cisplatin (Agarwal et al, 1999a).…”
Section: Statins In Cancer Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Lovastatin potentiated the antitumor effects of cisplatin in cellular and murine models of melanoma (Feleszko et al, 1998), increasing, at least partially, the apoptotic effect of oxaliplatin in human head and neck squamous cell carcinoma (SCC) (Mantha et al, 2003). In human colon cancer cell lines, the pretreatment with lovastatin increased the apoptotic death induced by cisplatin (Agarwal et al, 1999a).…”
Section: Statins In Cancer Treatmentmentioning
confidence: 99%
“…In human colon cancer cell lines (Agarwal et al, 1999a), but not in breast cancer cell lines (Mantha et al, 2003), the cytotoxic effects of 5-fluorouracil (5-FU) were potentiated by the combined use of lovastatin. Similar increases in 5-FU antiproliferative effects were also ob-STATINS AND CANCER: PROS AND CONS tained with atorvastatin or simvastatin combined with 5-FU in human non-small-cell lung cancer cell lines (Roudier et al, 2006) or in human myeloid leukemia cell lines (Ahn et al, 2008b), respectively.…”
Section: Statins In Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…EGFR inhibitors therefore seem very promising, but there are still a large number of questions about how to maximize their potential in cancer therapy. We have shown in preclinical studies that combining EGFR inhibitors with inhibitors of the mevalonate pathway may enhance their efficacy (16,17). This review describes the rationale and potential of using these inhibitors in combination to treat cancer.…”
Section: The Egfr As Atherapeutictargetmentioning
confidence: 99%
“…Targeting HMG-CoA reductase using lovastatin induces a potent tumor specific apoptotic response in a variety of tumor types including HNSCC-derived cell lines at therapeutically achievable levels of this drug (20,21). We recently showed that inhibiting EGFR function potentiated the apoptotic effects of lovastatin in HNSCC cells (22). The additive effects shown in HNSCC-derived cell lines suggested the possibility that these agents, although acting through distinct mechanisms, may share a common target.…”
Section: Introductionmentioning
confidence: 99%